2007
DOI: 10.1093/jac/dkm125
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing caspofungin plasma concentrations in patients of a surgical intensive care unit

Abstract: Our results show that body weight and albumin concentration influence caspofungin C(24) in SICU patients and should therefore be considered prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 40 publications
8
76
1
2
Order By: Relevance
“…In accordance with published data (21,(23)(24)(25)(26)(27)(28), the present PopPK analysis demonstrates that no dose adjustments of CAS are necessary on the basis of gender, age, or renal impairment as assessed by the creatinine clearance. As hepatic dysfunction impacts CL for adult patients with moderate hepatic impairment (ChildPugh score, 7 to 9), adjustment of the CAS dose on the basis of PK data is recommended (23,(27)(28)(29)(30).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In accordance with published data (21,(23)(24)(25)(26)(27)(28), the present PopPK analysis demonstrates that no dose adjustments of CAS are necessary on the basis of gender, age, or renal impairment as assessed by the creatinine clearance. As hepatic dysfunction impacts CL for adult patients with moderate hepatic impairment (ChildPugh score, 7 to 9), adjustment of the CAS dose on the basis of PK data is recommended (23,(27)(28)(29)(30).…”
Section: Discussionsupporting
confidence: 87%
“…Data reported by Migoya et al (10) for healthy adult subjects (dose, 100 mg; AUC, 227.4 mg · h/liter) as well as data published for standard CAS doses of 50 mg QD (AUC range, 83 to 114 mg · h/liter) indicate that the AUC values of the present study at the respective dose levels are only slightly higher (in the present study, the AUC for 100 mg CAS QD was 243 mg · h/liter and the AUC for 50 mg CAS QD was 121 mg · h/liter). For patients in a surgical intensive care unit, Nguyen et al (26) also observed slightly higher CAS trough levels than those for healthy subjects reported by Stone et al (31).…”
Section: Discussionmentioning
confidence: 75%
“…surgical ICU patients and to the PK parameters as calculated after multiple dosing in patients with moderate liver failure [4][5][6]. As shown, the AUC 0-24 is comparable to the one reported in healthy subjects; accumulation due to decreased hepatic metabolism resulting in a significantly higher systemic exposure (C 1h , C 24h , AUC 0-24 ) was not seen.…”
Section: Discussionmentioning
confidence: 63%
“…It has been shown, mostly through study of antibiotics, that the pharmacokinetic/pharmacodynamic profile of ICU patients is different from that of non-ICU controls, with large variations in the volume of distribution and renal clearance. Nguyen et al [26] analyzed the factors influencing caspofungin concentrations in ICU patients; they showed that body weight \75 kg and albumin concentration [23.6 g/l was associated with higher levels of caspofungin than predicted.…”
Section: Treatment Of Documented Infectionmentioning
confidence: 99%